ANALYSIS OF INVESTMENT CONTRIBUTION TOWARDS UNEMPLOYMENT AND POVERTY IN BATU CITY IN 2010-2012 - Silvi Asna Prestiana (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
Batu city is a city in East Java province which has great potential to develop into city with high economic growth. The Gross Regional Domestic Product (GRDP) at current process (ADHB) of Batu throughout the five year period reached IDR. 3,697,778 billion. By the condition of potential in Batu, investment activity in Batu looks more incentive with the amount of investment that has realizes more than 1 (one) Trillion Rupiah in 2010-2012. It affected to the number of unemployed people and poverty in Batu gradually decreased in a high trend in 2010-2012. Therefore the aims of this study are; (1) To know the existing effect of investment against unemployment in Batu city 2010-2012; (2) To know the existing effect of investment against poverty in Batu city 2010-2012. Analytical methods to answer this research is panel regression. Panel data is a combination of cross section data and time series data. Cross section Data consisting of multiple objects at a time, while the time series data is data arranged in order of time for an object. Based on regression panel test, investment to unemployment and poverty has significant influence simultaneously and partially. The increasing of investment in Batu city as much as 1%, will decline unemployment as much as 0.030%. On the other hand, The contribution of investment to poverty is 73.2%. Meanwhile, the diversity of poverty variables can be explained by the variable investment of 73.2%, or in other words the contribution of investment to influent poverty in Batu as much as 55.9%, while the remaining 27% is the contribution of the other variables that are not addressed in this study. The increasing of investment by 1%, will be able to decrease poverty as much as 0.117%. If the number of investment is constant, it will change poverty of Batu (3.645%). Meanwhile, the greater investment, so the lower poverty level of Batu city. Keywords: Investment, Unemployment, Poverty